2015
DOI: 10.3390/ijerph120303014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aminoglycoside Resistance and Virulence Genes among Enterococcus spp. Isolated from a Hospital in China

Abstract: This study investigated the aminoglycoside resistance phenotypes and genotypes, as well as the prevalence of virulence genes, in Enterococcus species isolated from clinical patients in China. A total of 160 enterococcal isolates from various clinical samples collected from September 2013 to July 2014 were identified to the species level using the VITEK-2 COMPACT system. The antimicrobial susceptibilities of the identified Enterococcus strains were determined by the Kirby-Bauer (K-B) disc diffusion method. PCR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
5
11
6
Order By: Relevance
“…On the other hand, Aph (2//)-Ib and Aph (2//)-Id were not detected in any isolates. This was in agreement with Wanxiang et al (2015) and Li et al (2015) who stated that 94.4% of HLAR enterococci were Aac (6/)-Ie-aph (2//)-Ia positive and in contrast to our results he detected Aph (2//)-Id in 1.3% of his HLAR enterococcal isolates and none of their strains were positive to Aph (2//)-Ic or Aph (2//)-Ib. Padmasini et al (2014) stated that Aac (6/)-Ie-aph (2//)-Ia found in 68.4% of their HLAR enterococcal isolates, while none of other genes were detected and attributed.…”
Section: Resultssupporting
confidence: 94%
“…On the other hand, Aph (2//)-Ib and Aph (2//)-Id were not detected in any isolates. This was in agreement with Wanxiang et al (2015) and Li et al (2015) who stated that 94.4% of HLAR enterococci were Aac (6/)-Ie-aph (2//)-Ia positive and in contrast to our results he detected Aph (2//)-Id in 1.3% of his HLAR enterococcal isolates and none of their strains were positive to Aph (2//)-Ic or Aph (2//)-Ib. Padmasini et al (2014) stated that Aac (6/)-Ie-aph (2//)-Ia found in 68.4% of their HLAR enterococcal isolates, while none of other genes were detected and attributed.…”
Section: Resultssupporting
confidence: 94%
“…Moreover, 8.1% of the HLGR enterococcal isolates did not carry any of the examined AME genes. This was lower than that previously reported by Li et al [19].…”
Section: Discussioncontrasting
confidence: 67%
“…Institutional ethical clearance was obtained. The specimens were isolated from various clinical samples, as described previously (10), including urine (9/13), orotracheal fluid (1/13), vaginal/semen swab (1/13), pus (1/13) and blood (1/13). A VITEK 2 Compact system (BioMérieux, Ltd., Marcy l'Etoile, France) and polymerase chain reaction (PCR) analysis were used to identify E. faecium.…”
Section: Bacterial Strains and Identification A Total Of 13 Clinicalmentioning
confidence: 99%